COMPARATIVE GENOME OF TWO STRAIN MORAXELLA CATARRHALIS USING IN SILICO ANALYSIS - Aji, Oktira Roka (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Moraxella catarrhalis can cause otitis media and exacerbations of chronic obstructive pulmonary disease in human. Here we describe the comparison between two publicly available genomes of two strain of M.catarrhalis using computational analysis to obtain genomic features between them. Comparative genomic analysis were carried out using available tools in public domain websites. The aim of this study was to investigate the differences and similarities between two strains by comparing their genomic sequences. The results indicated that may be used to offer better understanding M.catarrhalis lifestyle.Â Keywords: Moraxella catarrhalis; In Silico; Comparative genome analysis